Evaluation of impact of 23 valent pneumococcal polysaccharide vaccine following 7 valent pneumococcal conjugate vaccine in Australian Indigenous children. Issue 48 (27th November 2015) - Jayasinghe, Sanjay; Chiu, Clayton; Menzies, Rob; Lehmann, Deborah; Cook, Heather; Giele, Carolien; Krause, Vicki; McIntyre, Peter
Abstract: Background: High incidence and serotype diversity of invasive pneumococcal disease (IPD) in Indigenous children in remote Australia led to rapid introduction of 7-valent conjugate pneumococcal vaccine (7vPCV) at 2, 4 and 6 months in 2001, followed by 23-valent polysaccharide pneumococcal vaccine (23vPPV) in the second year of life. All other Australian children were offered 3 doses of 7vPCV without a booster from 2005. This study evaluated the impact of the unique pneumococcal vaccine schedule of 7vPCV followed by the 23vPPV booster among Indigenous Australian children. Methods: Changes in IPD incidence derived from population-based passive laboratory surveillance in Indigenous children <5 years eligible for 23vPPV were compared to non-Indigenous eligible for 7vPCV only from the pre-vaccine introduction period (Indigenous 1994–2000; non-Indigenous 2002–2004) to the post-vaccine period (2008–2010 in both groups) using incidence rate ratios (IRRs) stratified by age into serotype groupings of vaccine (7v and 13vPCV and 23vPPV) and non-vaccine types. Vaccine coverage was assessed from the Australian Childhood Immunisation Register. Results: At baseline, total IPD incidence per 100, 000 was 216 ( n  = 230) in Indigenous versus 55 ( n  = 1993) in non-Indigenous children. In 2008–2010, IRRs for 7vPCV type IPD were 0.03 in both groups, but for 23v-non7v type IPD 1.2 (95% CI 0.8–1.8) in Indigenous versus 3.1 (95% CI 2.5–3.7) in non-Indigenous, difference driven primarily by serotype 19A IPD (IRR 0.6 in Indigenous versus 4.3 in non-Indigenous). For non-7vPCV type IPD overall, IRR was significantly higher in those age-eligible for 23vPPV booster compared to those younger, but in both age groups was lower than for non-Indigenous children. Conclusion: These ecologic data suggest a possible "serotype replacement sparing" effect of 23vPPV following 7vPCV priming, especially for serotype 19A with supportive evidence from other immunogenicity and carriage studies. Applicability post 10vPCV or 13v PCV priming in similar settings would depend on local serotype distribution of IPD.